Предмет: Алгебра,
автор: lelchikmilka
1. (x-7)^2=(9-x)^2
2. 2x-5x^2+7=0
Ответы
Автор ответа:
1
Ответ:
1. х=8
2. ====1,4
==== -1
Объяснение:
1. (х-7)²=(9-х)²
х²-14х+49=81-18х+х²
х²-14х-х²+18х=81-49
4х=32
х=8
2. 2х-5х²+7=0
-5х²+2х+7=0 |:(-1)
5х²-2х-7=0
D=b²-4ac=(-2)²-4*5*(-7)=4+140=144
==12
====1,4
==== -1
Автор ответа:
1
Ответ:
1.(х-7)^2=(9-х)^2
49+х^2-14×х=(9-х)^2
(х-7)^2=81+х^2-18×х
-32+4×х=0
4х=32
х=32/4
Объяснение:
второе нещнаю
Похожие вопросы
Предмет: Українська мова,
автор: Anya1w
Предмет: Математика,
автор: h6932626
Предмет: Физика,
автор: rimiii
Предмет: Английский язык,
автор: Smailova2009
Предмет: Математика,
автор: Rtyfugekgr4